PMG658 : Community organization / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2020)
This course will explore the potential and importance of community and organizations in park and recreation development and management. Methods to involve the importance of public involvement in their planning and management. This process is a bridge between community and organizations to resolve conflict.